Major Conditions of Shooting Range Operation in Poland - Józef GACEK (Najistotniejsze uwarunkowania związane z eksploatacją strzelnic w Polsce, 2018)
Under the “Authorisations of the Minister of National Defence” (latest – No. 57/MON dated 22 December 2014), a Permanent Expert Team operates at the Institute of Armament Technology of the Faculty of Mechatronics and Aerospace of the Military University of Technology (Warsaw, Poland), performing test shootings for the purpose of verifying the fulfilment of technical requirements to be met by garrison shooting ranges and their locations. During almost 20 years of its activity, the Team has conducted research studies under more than 325 civil law contracts concluded with operators of shooting ranges, numerous expert analyses and prepared specialist opinions for courts and prosecutor's offices, and participated in the creation of normative acts and documents, concerning – among others – provision of safety of the operated field training facilities, mainly garrison and training ground shooting ranges. The results of the Team's work have been used, among others, by the Ministry of National Defence (with the active participation of the Team) to prepare regulations of the Minister of National Defence concerning the technical conditions to be met by garrison shooting ranges and their locations. The first of these regulations was issued on 4 October 2001 (Polish Journal of Laws of 2001, no. 132, item 1479), and its latest revision on 15 December 2017 (Polish Journal of Laws of 2018, item 113). The paper presents selected results of studies of the Permanent Expert Team related to, among others, ensuring the safety of users of garrison and training ground shooting ranges, which form a part of the field training facilities of the Armed Forces of the Republic of Poland, the Police, the Border Guard, the Customs Service, security companies, hunting and sports organisations. Of particular value are the conclusions and propositions of the Expert Team related to, for example: improvement of quality of the law created in Poland, concerning in particular training facilities; ensuring safety at shooting ranges during training with firearms of various types and calibres, utilising various types of ammunition; expert supervision over construction, acceptance and operation of shooting ranges; principles of safe operation of shooting ranges, ensuring longevity of the facilities, etc.
Keywords: Bezpieczeństwo eksploatacji strzelnic